Alternative ways of teaching algorithms - Dagienė, Valentina (Lietuvos matematikos rinkinys, 2000)
This paper deals with ways of teaching algorithms in basic comprehensive school. Three main methods are described: the programming language Pascal, graphical schemes, and Logo. The main attention is paid to the analysis of using Logo for developing algorithms in elementary informatics course for IX–X grade students. The basic algorithmical constructions: variables, assignment, conditional statements, loops, procedure are described.